Currentevoltage characteristics of electrochemically synthesized multi-layer graphene with polyaniline - Awasthi, Seema (H. : ĐHQGHN, 2018)
Graphene nanosheets (GNS) synthesized through commercially available pencil lead were used to pre-pare composites with polyaniline on ITO coated PET substrate. IeV characteristics of the GNS-PANI composite device shows a decrease in band gap of PANI from 2.8 eV to 6.9 meV at 15 wt% loading of GNS in PANI. SEM and Raman spectroscopy show good dispersion of GNS and interfacial interaction with the GNS-PANI composite by a significant shift in the G peak at 15 wt% GNS-PANI, further confirming the formation of the composite at 15 wt%. Instead of the in-situ polymerization process, the polymer and graphene were mixed externally in the desired concentrations and cast on the substrate directly, thereby offering a good control over the composition of the composite material.